Analisa Dampak Motivasi, Inovasi, dan Lokasi Pada Keberhasilan Usaha Kue Tradisional Holala Kota Jambi - Evi Fauzani; Etty Siswati (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2020)
The purpose of this study was to analyze the influence of motivation , innovation and location on the success of the Holala Traditional Cake in Jambi City . This type of research is quantitative - descriptive . Quantitative method is a method that use quantitative analysis tools , where the results of the analysis are presented in the form of numbers which are explained and interpreted in a description , while descriptive method is a method that describes a set of data that will be made , both by researchers themselves and in groups, researchers use SPSS 22 to test the research . The population and sample in this study were employees of Holala Traditional Cakes with 20 respondents . Data collection technique that used was questionnaire . Results of this study are significant influence of motivation for business success because t count > t table (-3.294> 2.119) and resulting significant value (0.005 & lt;0.05). Innovation has no significant effect on business success due to t count < t table (0.706 & lt ; 2.119) and the resulting significant value (0.491 & gt ; 0.05). Location has a significant effect on business success due to t count > t table (20,365> 2,119) and the resulting significant value (0,000 & lt ; 0.05). Motivation , innovation , and location simultaneously have a significant effect on business success , because the results of the f test carried out resulting the value of count & gt ; f tabel ( 176.787 & gt ; 3.24) and with significant value generated (0,000 & lt ;0.05).